2016
DOI: 10.1016/j.neuron.2016.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Circuit-wide Transcriptional Profiling Reveals Brain Region-Specific Gene Networks Regulating Depression Susceptibility

Abstract: Summary Depression is a complex, heterogeneous disorder and a leading contributor to the global burden of disease. Most previous research has focused on individual brain regions and genes contributing to depression. However, emerging evidence in humans and animal models suggests that dysregulated circuit function and gene expression across multiple brain regions drive depressive phenotypes. Here we performed RNA-sequencing on 4 brain regions from control animals and those susceptible or resilient to chronic so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
322
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 306 publications
(368 citation statements)
references
References 69 publications
21
322
4
Order By: Relevance
“…In vivo, one of the members of this family of proteins, NeuroD2, was found at MR-, but not at GR-exclusive binding sites (van Weert et al 2017). The NeuroD2 proteins have a role in neuronal differentiation and studies with NeuroD2 mutants revealed their role in stress susceptibility (Bagot et al 2016).…”
Section: Molecular Studiesmentioning
confidence: 99%
“…In vivo, one of the members of this family of proteins, NeuroD2, was found at MR-, but not at GR-exclusive binding sites (van Weert et al 2017). The NeuroD2 proteins have a role in neuronal differentiation and studies with NeuroD2 mutants revealed their role in stress susceptibility (Bagot et al 2016).…”
Section: Molecular Studiesmentioning
confidence: 99%
“…Dysregulation of biological pathways and functional gene sets contribute to manifestation of depression-related behaviors 26 In contrast to GO, classification by Gene Set Enrichment Analysis (GSEA) is designed to detect changes in groups of functionallyrelated genes whose expression is coordinately regulated 30,31 . GSEA analysis revealed that low-dose ketamine alters the expression of diverse gene sets involved in GPCR signaling, neuronal metabolism, vascularization, and structural plasticity ( Figure 3B).…”
Section: Profiling the Translatome After Antidepressant Ketaminementioning
confidence: 99%
“…Given such predictions, we sought to examine the precise relationship between H3.3 differential enrichment and alterations in gene expression that may influence the activation or inhibition of these functional biological processes. To do so, odds ratio analyses were performed comparing H3.3 ChIP-seq analyses with corresponding published mRNA expression data (21). We found that, although acute stress leads to roughly as many changes in H3.…”
mentioning
confidence: 99%